Kritik Ilmu Kalam Terhadap Pandangan Serkualisme Ilmiah - Dwi Januarti; Arjuna Samudra; Rina Risti Ningsi; Cantika Ananda Sopyan; Muhammad Parhun (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This study explores the critical perspective of Islamic Kalam (theology) on scientific secularism, a worldview that separates religion from scientific inquiry and public life. Using a qualitative literature review method, the research analyzes both classical and contemporary Kalam texts alongside modern critiques of secularism. The findings reveal that Kalam theology fundamentally rejects the dichotomy between religious knowledge and scientific knowledge, emphasizing the complementary relationship between divine revelation and human reason. Kalam scholars argue that secularism undermines the moral and spiritual values essential for holistic knowledge and societal well-being. This paper concludes that Kalam offers a robust epistemological framework to counter the challenges posed by secularism, promoting an integrated approach that harmonizes faith and reason in addressing modern scientific and social issues.